Identifikasi Faktor-Faktor Penyebab Penurunan Aktivitas Perdagangan Mebel di Koridor Jalan Soekarno Hatta Kabupaten Jepara - Divya Liantina; Samsul Ma'rif (Jurnal Wilayah dan Lingkungan, 2016)
The spatial use in Jepara District is dominated by the local export-oriented furniture industries. Soekarno Hatta corridor functions as furniture showrooms but in fact, its functionality was decreasing because many were closed down. The study aims to identify the causing factors related to functional downgrade of the area to perform as a furniture trade area.The study employed a qualitative approach with descriptive, scoring, and mapping analyses. The results showed that the dominant causing factor wastrading shift to online marketing, direct purchase to the furniture craftsmen, and seasonal school holiday and Eid al-Fitr celebration. It indicates that the functioning of certain trading area is influenced by product marketing medium, consumers' product awareness, and the purchasing power parity of the consumers.